The A-Z of modern architecture. - Gössel, Peter, 1956- (Köln : Taschen, 2007)
An unprecedented architecture encyclopedia Unlike most architecture encyclopedias, which tend to concentrate more on buildings and floor plans than their designers, this tome puts the architects in the spotlight, profiling individuals so that readers can get a clear overview of their bodies of work. Each architect's entry features a portrait, quote, and short biography as well as a description of important works, historical context, and general approach; illustrations include numerous drawings, photographs, and floor plans. The book's A to Z entries cover not only architects but also groups, movements, and styles from the 18th to the 21st centuries. With 600 entries and 5,200 illustrations, The A-Z of Modern Architecture is a comprehensive resource that no architecture professional, fan, or student should be without. Features: 566 architects from the 18th to the 21st century Architect portrait, quote, and short biography Description of important works, historical context, and general approach Numerous drawings, photographs, and plans
Keywords: Architectuur -- Biografieënverzamelingen; Architectuur -- 19de eeuw; Architectuur -- 20ste eeuw